Kinetics of Graphene and 2D Materials Growth - Dong, Jichen; Zhang, Leining; Ding, Feng (Advanced materials (Weinheim), 2019)
During the last 10 years, remarkable achievements on the chemical vapor deposition (CVD) growth of 2D materials have been made, but the understanding of the underlying mechanisms is still relatively limited. Here, the current progress on the understanding of the growth kinetics of 2D materials, especially for their CVD synthesis, is reviewed. In order to present a complete picture of 2D materials' growth kinetics, the following factors are discussed: i) two types of growth modes, namely attachment‐limited growth and diffusion‐limited growth; ii) the etching of 2D materials, which offers an additional degree of freedom for growth control; iii) a number of experimental factors in graphene CVD synthesis, such as structure of the substrate, pressure of hydrogen or oxygen, temperature, etc., which are found to have profound effects on the growth kinetics; iv) double‐layer and few‐layer 2D materials' growth, which has distinct features different from the growth of single‐layer 2D materials; and v) the growth of polycrystalline 2D materials by the coalescence of a few single crystalline domains. Finally, the current challenges and opportunities in future 2D materials' synthesis are summarized. Growth of 2D materials is edge dependent and affected by a number of factors, such as substrate, H2 and O2 in the growth atmosphere, defects, coalescence of grains, etc. Mechanisms underlying the growth kinetics of 2D materials are systematically discussed, and the effects of various factors are summarized. In addition, progress on 2D materials' etching is also presented.